Soil Contamination from Cassava Wastewater Discharges in a Rural Community in the Niger Delta, Nigeria - Q-AL Izonfuo; PA Bariweni; DMC George (Journal of Applied Sciences and Environmental Management)
Ten soil samples were collected with a 9mm Dutch auger along two transects for six months for the purposes of investigating the effects of cassava wastewater on the physico-chemical characteristics of soils around a cassava processing plant in a rural community in the Niger Delta. It was observed that the addition of cassava wastewater to the soil resulted to changes in the parameters. Mean Mg level of the soil samples was lower than the mean in the control soil samples. Correlation analysis shows that soil pH influenced CN- (r = 0.18); K (r = 0.17); Ca (r = 0.97); Mg (r = 0.13); Na (r = 0.03); P (r = 0.08); N (r = 0.40); Organic Carbon (r = 0.08) and organic matter (r = 0.06). The cyanide levels in the soils were found to be higher than the recommended limits for agriculture and other purposes. Also, amongst the exchangeable bases, Mg was significantly influenced by cassava wastewater discharges. The implications of these variations on agriculture and other activities have been appraised.